High resolution measurement of physical variables change for INS - Hernández Perdomo, W. (2017)
Fast and accurate measurement of physical variables is critical for many systems. Inertial navigation systems (INS) are components of paramount importance for aerial vehicles, one of the tasks of INS is to determine the position of the moving particle. The INS has an Inertial Measurement Unit (IMU), where there are sensors, in particular accelerometers which allow the IMU to calculate speed and position, just by integrating the measured acceleration. Accelerometers have a frequency domain output, this makes them a particular case of Frequency domain sensors (FDS). As it is well known in metrology of time-frequency, when measuring a frequency source, more time is required if more accuracy is needed. For a device which is moving at high speed, a delay in the measurement of any of its parameters could lead to a delay in the controls response. For this reason, the purspose of this work is to show how to reduce the time required for measuring the output from an accelerometer inside an IMU. In particular, this work deals with the task of improving resolution, speed and quality of measurements of FDS. This is done by using the rational approximations principle and theory developed by our research group.